Mindfulness and Well-Being: The Role of Buddhist Practices in Mental Health Care in Thailand - พระราชพัฒนวัชรบัณฑิต (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
Mindfulness, deeply rooted in Buddhist practices, plays a significant role in mental health care in Thailand, offering a holistic alternative to conventional approaches. This paper explores how mindfulness-based techniques, drawn from Buddhist teachings, enhance emotional regulation, resilience, and overall well-being. The integration of traditional Buddhist practices with modern mental health care models demonstrates their effectiveness in addressing stigma, promoting emotional control, and fostering community well-being. By examining case studies from Thai Buddhist temples and educational institutions, this research highlights the benefits of combining mindfulness with conventional therapies and its impact on mental health outcomes. The findings emphasize the need for culturally sensitive approaches that respect Thailand’s spiritual heritage while advancing mental health care strategies.